Cannabinoids as a possible alternative in the treatment of psoriasis (Research, Society and Development, 2022)
With strong genetic predisposition, relationship with the environment and autoimmune pathogenic traits, psoriasis is a chronic, non-infectious disease that affects people regardless of age or gender. Treatment aims to control the differentiation and proliferation of keratinocytes. With this in mind, the objective of this narrative review is to analyze the existing literature involving the effects of Cannabis sativa in the treatment of the disease, focusing on its effectiveness. An active search in Google Scholar, Pubmed and LILACS databases showed that cannabinoids have therapeutic potential in psoriasis, mainly in relation to the proliferation of keratinocytes and the modulation of inflammation, but most of the available studies are in vitro. More clinical studies in humans are needed for better elucidation, so that cannabinoids can be recommended as a safe and effective treatment in psoriasis.